On The Farthest Point Problem In Hilbert Spaces (European Journal of Pure and Applied Mathematics, 2023)
In an attempt to solve the farthest point problem, we introduce a new class of uniquely remotal sets. Namely, the class of uniquely distant sets. Then, we prove that in a separable Hilbert space, every uniquely distant set is a singleton.
Keywords: Farthest points; Uniquely remotal sets